2013
DOI: 10.1515/hsz-2012-0322
|View full text |Cite
|
Sign up to set email alerts
|

Glucocerebrosidase, a new player changing the old rules in Lewy body diseases

Abstract: Mutations in the gene encoding glucocerebrosidase ( GBA1 ) cause Gaucher disease (GD), a lysosomal storage disease with recessive inheritance. Glucocerebrosidase (GCase) is a lysosomal lipid hydrolase that digests glycolipid substrates, such as glucosylceramide and glucosylsphingosine. GBA1 mutations have been implicated in Lewy body diseases (LBDs), such as Parkinson ' s disease and dementia with Lewy bodies. Parkinsonism occurs more frequently in certain types of GD, and GBA1 mutation carriers are more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 88 publications
(107 reference statements)
0
9
0
1
Order By: Relevance
“…Several potential mechanisms leading to α-synuclein aggregation have been proposed. 12 Elucidation of the mechanism underlying the pathogenic actions of GBA1 mutations will help us identify rational therapeutic strategies for LBDs and GD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several potential mechanisms leading to α-synuclein aggregation have been proposed. 12 Elucidation of the mechanism underlying the pathogenic actions of GBA1 mutations will help us identify rational therapeutic strategies for LBDs and GD.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have shown that heterozygous carriers of mutations in GBA1 are at higher risk for PD than the general population. 12 For example, patients with PD are approximately five times more likely to carry GBA1 mutations than healthy control subjects. 13 Compared with control group, the incidence of parkinsonism is increased 6- to 17-folds in patient group with type1 GD.…”
Section: Introductionmentioning
confidence: 99%
“… 38 Heterozygous carriers of GBA1 mutations are at a higher risk for PD. 39 , 40 It has been shown that about 75% of Lewy bodies, a pathological hallmark of PD, colocalized with GCase 1 in brains of PD and DLB patients with heterozygous GBA1 mutations. 41 These results suggest that lysosomal enzyme deficiency is associated with the development of PD.…”
mentioning
confidence: 99%
“…Several genes linked to PD have been suggested to function in the lysosomal degradation pathway and in formation of α-synuclein pathology [ 42 , 43 , 44 ]. Here, we generated a human neuroblastoma cell line lacking ATP13A2 and investigated the role of this protein in the general lysosomal function and in α-synuclein metabolism.…”
Section: Introductionmentioning
confidence: 99%